Volume 4: 8th International Conference on Multibody Systems, Nonlinear Dynamics, and Control, Parts a and B 2011
DOI: 10.1115/detc2011-47578
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Sensitivity Analysis for Multibody Dynamics Systems Using an Iterative Steps Method With Application in Topology Optimization

Abstract: Efficient and reliable sensitivity analyses are critical for topology optimization, especially for multibody dynamics systems, because of the large number of design variables and the complexities and expense in solving the state equations. This research addresses a general and efficient sensitivity analysis method for topology optimization with design objectives associated with time dependent dynamics responses of multibody dynamics systems that include nonlinear geometric effects associated with large transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is concluded that the iterative sensitivity analysis method gives the sensitivity same as the AVM method and the time integration incorporated method based on the Generalized-α algorithm. 14,17,18 Figure 5 shows the time history of sensitivities of first eight interactive members. It can be seen that the sensitivities calculated by the iterative method is same as the time integration incorporated method and the AVM method in all the time duration.…”
Section: Optimization Algorithmmentioning
confidence: 99%
“…It is concluded that the iterative sensitivity analysis method gives the sensitivity same as the AVM method and the time integration incorporated method based on the Generalized-α algorithm. 14,17,18 Figure 5 shows the time history of sensitivities of first eight interactive members. It can be seen that the sensitivities calculated by the iterative method is same as the time integration incorporated method and the AVM method in all the time duration.…”
Section: Optimization Algorithmmentioning
confidence: 99%